Pemanfaatan Konteks Digital Sehari-hari sebagai Media Otentik dalam Pembelajaran Bahasa Arab untuk Generasi Gen-Z. - Muhammad Paozan; Dedy Wahyudin (Pascasarjana Universitas Islam Negeri Mataram, 2026)
Learning Arabic has an important role in the world of Islamic education because it is used as the language of the Qur'an, hadith, and various Islamic literature. However, learning Arabic still faces various obstacles, such as learning that is too theory-oriented and a lack of communication practices in daily life. This condition causes students to have difficulty using Arabic actively and communicatively. This study aims to describe the application of daily context in Arabic language learning and to find out its influence on students' communication skills. This study uses a descriptive qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The research data source consists of primary data from teachers and students and secondary data in the form of books, journals, and other supporting documents. The results of the study show that the application of daily context in learning Arabic can be carried out through daily conversations, classroom activities, school or pesantren environment, the use of social media and technology, as well as worship and cultural activities. The contextual approach is able to improve students' speaking, listening, and vocabulary mastery skills so that learning becomes more communicative, interactive, and effective.